Diversity in Health Care: A Case of Diversity in Long-Term Care - Fuqua, Ronald M.; McIlwain, Thomas; Smith, Kendolyn; Walden, Latrina (Archives of Business Research, 2019)
Achieving diversity is a necessity in any organization but is especially important in long-term care. The care delivered is to a diverse group of patients and their families. Therefore, this case allows the analysis of diversity in one long-term care company. While Federal EEO requirements include a report of diversity annually for employers and contractors, this is a further analysis of the diversity data used for reporting. Looking into frequency and distributive statistics allows a better understanding of the diversity of this company.